l-Tryptophan Production by Achromobacter liquidum - Ujimaru, Toshihiko (1983)
Conditions for the production of tryptophanase from Achromobacter liquidum and for the conversion of l-serine and indole to l-tryptophan were studied. The enzyme could be produced in amounts as great as 0.750 U/ml (degradation) and 0.294 U/ml (synthesis) by shaking cultures at 30°C in a medium containing dextrin, yeast extract, l-tryptophan, and l-glutamic acid. l-Tryptophan was produced most efficiently by shaking the cells at 37°C in a reaction mixture containing 60 mg of l-serine per ml, 60 mg of indole per ml, and 0.5 mM pyridoxal phosphate. After 3 days, 96 mg of l-tryptophan per ml was formed, and l-tryptophan was easily isolated to 85.4% yield by concentration of the reaction mixture.